IMPROVING STUDENTS’ VOCABULARY MASTERY BY USING QUIZIZZ APPLICATION IN JUNIOR HIGH SCHOOL - Emelia, Tengku Winona; Silaen, Vidra Azzahra Falna Raysa; Manurung, Imelda Darmayanti (Universitas Islam Negeri Sumatera Utara Medan, 2024)
This study was aimed to examine on how Quizizz application can be utilized to enhance students' vocabulary mastery and determine whether there is improvement in their vocabulary skills as the result of using the Quizizz application. It was conducted in Madrasah Tsanawiyah Negeri 2 Asahan in 2023; 32 students from the 1st grade in class VII-A took part as the participants. Classroom Action Research was employed for this study and divided into two cycles. The data was collected by using qualitative methods; such as observation, interview, diary notes, and documentation, as well as quantitative methods; such as multiple-choice tests, that conducted at the end of each cycle. Based on the result, the students' scores increased from the first cycle to the last cycle. The pre-test mean was 55.31, and 7 students (21.87%) scored over 75 points. The post-test for cycle I was 72.50, that higher than the pre-test, and 19 students (59.37%) scored over 75 points. The post-test mean for cycle II was 91.87, that higher than the post-test for cycle I, and 31 students (3.12%) scored over 75 points. They did not encounter any significant challenges. The assessment of attitudes was evaluated with a maximum score as 160. The students scored as 141 in care, 134 in respect, 139 in teamwork, 134 in self-confidence, and 138 in responsibility. They indicated that the using of Quizizz application to improve students' vocabulary mastery was effective. Based on the test results and observations toward students, their enthusiasm and excitement are also increased